A single-cell transcriptome analysis reveals astrocyte heterogeneity and identifies CHI3L1 as a diagnostic biomarker in Parkinson's disease - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Yang Yao; Sijia Wang; Yuan Wang; Zhiyun Wang (Heliyon)
Background: Parkinson's disease (PD) is the second most common neurodegenerative disease, characterized by motor and non-motor symptoms. It has been reported that astrocytes play a critical role in the pathogenesis and progression of PD. Here, we aimed to identify the heterogeneity of astrocytes and investigate genes associated with astrocyte differentiation trajectories in PD. Methods: The single-cell transcriptomic profiles of PD samples were collected from the GEO database. We have identified subsets of astrocytes and analyzed their functions. The differentiation trajectory of astrocyte subtypes was explored using Monocle2. Inflammatory response scores were determined using AUCell. The levels of CHI3L1 mRNA and protein expressions in astrocytes were analyzed using qRT-PCR and Western Blot assay, respectively. Results: We characterized seven cell types within the substantia nigra region of both PD and normal samples. Our analysis revealed that astrocytes comprised the second-highest proportion of cell types. Additionally, we identified three distinct subpopulations of astrocytes: Astro-C0, Astro-C1, and Astro-C2. Notably, Astro-C0 was associated with inflammatory signaling pathways. Trajectory analysis indicated that Astro-C0 occupies an intermediate stage of differentiation. The astrocyte-related gene CHI3L1 was found to be highly expressed in the Astro-C0 subpopulation. Furthermore, we observed increased levels of CHI3L1 mRNA and protein in LPS-induced astrocytes. Astrocytes exhibiting elevated CHI3L1 levels demonstrated interactions with microglia in PD patients. Lastly, we discovered that CHI3L1 was significantly overexpressed in PD patients and exhibited strong diagnostic potential for the disease. Conclusion: This study clarified the heterogeneity of astrocytes in PD based on the single-cell transcriptomic profiles and found that CHI3L1 may be a diagnostic biomarker for PD.